Biomechanical and physiological effects of passive upper limb exoskeletons in simulated manufacturing tasks - Francesco Scotto di Luzio; Christian Tamantini; Raffaele Di Maro; Chiara Carnazzo; Stefania Spada; Francesco Draicchio; Loredana Zollo (Wearable Technologies)
In the last two decades, the adoption of exoskeletal devices for the reduction of the biomechanical overload of workers has hugely increased. They allow relief of the biomechanical load of the operator and ensure the operator’s contact with the object without binding its interaction. In this work, the biomechanical and physiological effects on the user wearing upper limb passive exoskeletons have been evaluated to highlight the benefits and possible drawbacks introduced by their use in typical manufacturing tasks. MATE and PAEXO Shoulder passive exoskeletons have been assessed during the execution of different working gestures among static, dynamic, and quasi-static tasks on 16 healthy volunteers. The obtained results confirm that the adoption of such systems significantly impacts the users by reducing the muscular load, increasing endurance, and reducing the perceived effort. Moreover, this analysis pointed out the specific benefits introduced by one exoskeleton with respect to the other according to the specific task. The MATE has the potential to reduce muscle load during the execution of static tasks. Conversely, the PAEXO Shoulder positively impacts the users’ biomechanical performances in dynamic tasks.